2002
DOI: 10.1002/ana.10312
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that accumulation of ceramides and cholesterol esters mediates oxidative stress–induced death of motor neurons in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is characterized by degeneration of motor neurons in the spinal cord resulting in progressive paralysis and death. The pathogenic mechanism of ALS is unknown but may involve increased oxidative stress, overactivation of glutamate receptors, and apoptosis. We report abnormalities in sphingolipid and cholesterol metabolism in the spinal cords of ALS patients and in a transgenic mouse model (Cu/ZnSOD mutant mice), which manifest increased levels of sphingomyelin, ceramides, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
234
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 267 publications
(258 citation statements)
references
References 52 publications
20
234
2
2
Order By: Relevance
“…In contrast, our analysis of cervical spinal cord gray and white matter samples showed that the major isoforms of Cer, GalCer, GlcCer, LacCer, GM3, GM1, GL3, and SPM were significantly elevated in ALS patients. These findings corroborate an earlier study that evaluated Cer and SPM levels in human ALS spinal cords (29). Importantly, we also showed that GSL-related pathology in ALS patients was not due to a reduction in the activity of the enzymes that mediate their degradation (as is observed in lysosomal storage diseases); acidic enzymatic activities of GBA1, GBA2, HEX, GALC, α-GAL, and β-GAL were all significantly increased in ALS spinal cord samples.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, our analysis of cervical spinal cord gray and white matter samples showed that the major isoforms of Cer, GalCer, GlcCer, LacCer, GM3, GM1, GL3, and SPM were significantly elevated in ALS patients. These findings corroborate an earlier study that evaluated Cer and SPM levels in human ALS spinal cords (29). Importantly, we also showed that GSL-related pathology in ALS patients was not due to a reduction in the activity of the enzymes that mediate their degradation (as is observed in lysosomal storage diseases); acidic enzymatic activities of GBA1, GBA2, HEX, GALC, α-GAL, and β-GAL were all significantly increased in ALS spinal cord samples.…”
Section: Discussionsupporting
confidence: 92%
“…The homogenate was centrifuged at 1,000 ϫ g for 15 min at 4°C and the nuclear pellet was washed one time and then discarded. The combined original and wash supernatants were centrifuged at 100,000 ϫ g for 1 h and the resulting crude membrane pellet was quick-frozen and stored at 4 C. Before lipid extraction, the membrane samples were normalized based on an average wet weight of Ϸ19 mg. Electrospray tandem MS analyses were performed by using methods described (16).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it seems that p75 NTR is able to activate different SMases depending on the cell type. Interestingly, the spinal cord of ALS patients and SOD1 G93A mice exhibit a remarkable increase in ceramides and cholesterol esters, which have been shown to sensitize motor neurons to different death stimuli including oxidative and excitotoxic insults (Cutler et al, 2002). Therefore, NGF signaling through p75 NTR and the subsequent increase in ceramide production may also modulate the sensitivity of motor neurons to other apoptotic stimuli.…”
Section: Reexpression Of P75mentioning
confidence: 99%